2013
DOI: 10.1075/sin.19.04cha
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation in Mandarin Chinese children’s personal narratives

Abstract: Evaluation is a critical component of personal narrative, the component that conveys to listeners how narrators feel about experiences that happened to them. Evaluation conveys the impact of what actually did happen in the context of what narrators expected would happen but did not or what they wished had happened instead. This chapter presents a study of how Taiwanese children develop the ability to evaluate their narratives and a comparison of Taiwanese to English-speaking children in their use of evaluative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…By scrutinizing such narratives and the shifts within them via the Narrative Dimensions Model, researchers may really bring to the fore the intricate, usually non-arbitrary, multi-dimensional nature of narratives (for examples, see Van De Mieroop, forthcoming). In addition, the model will enable researchers to identify potential cultural differences in narration (see e.g., Chang & McCabe, 2013). As such, this model can account in a more detailed way for the intra-and inter-genre variation that is typical of real-life narratives across various cultures, because it highlights dimensional differences as well as similarities between various narratives that may otherwise go unnoticed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By scrutinizing such narratives and the shifts within them via the Narrative Dimensions Model, researchers may really bring to the fore the intricate, usually non-arbitrary, multi-dimensional nature of narratives (for examples, see Van De Mieroop, forthcoming). In addition, the model will enable researchers to identify potential cultural differences in narration (see e.g., Chang & McCabe, 2013). As such, this model can account in a more detailed way for the intra-and inter-genre variation that is typical of real-life narratives across various cultures, because it highlights dimensional differences as well as similarities between various narratives that may otherwise go unnoticed.…”
Section: Discussionmentioning
confidence: 99%
“…Fourthly, the comparative study of narratives of personal experience in various cultural contexts has also revealed many variations vis-à-vis Labov and Waletzky's (1966) description of stories. For example, it was found that Asian children's narratives differed from American children's in various ways, e.g., Japanese children focus more on "collections of experiences" in their stories (Minami & McCabe, 1995), which is also the case for Taiwanese children, who were also found to evaluate their narration less (Chang & McCabe, 2013). Of course, these variations cause problems when attempting to fit these narratives into the "narrow" definition by Labov and Waletzky, nor do these narratives always constitute a genre that is entirely different from the narrative of personal experience.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout childhood, sharing personal narratives is important for building and maintaining friendships, for socio-emotional wellbeing, and for participating in classroom discussions or peer conversations. Children's use of evaluative devices when conveying personal narratives has been the subject of numerous research studies since Labov's [3] landmark study in the 1960s (e.g., [4][5][6][7][8][9]). However, sample sizes in these studies were relatively small, ranging from 16 to 41 per age or other subgroup, and a wide range of elicitation tasks and prompts have been used.…”
Section: Introductionmentioning
confidence: 99%
“…The range of linguistic devices to express these relations includes conjunctions, adverbs, and tense. Chang and McCabe (2013) looked at the connectives used by different age groups of Taiwanese children learning English as a foreign language and found that older children expressed more causal relations in their stories than did younger children.…”
Section: Development Of Narrative Abilitymentioning
confidence: 99%